How clickbait is used on Depor.com to inform about the probable transfer of Paolo Guerrero to Boca Juniors between november 2019 and january 2020 - Melgar Sandoval, Héctor Alberto (2021)
This research work shows how the Peruvian sports newspaper Depor.com repeatedly uses clickbait. It is understood as click hook, because of its translation into English; as a strategy of sensationalism to report on the possible transfer of Paolo Guerrero to Boca Juniors between November 2019 and January 2020. This action of the Peruvian newspaper produces a current of disinformation in the digital ecosystem and generates a new language that has as main characteristics: Very attractive and exaggerated headlines with uneven breakdown or content linked to speculation and interpretation. In this way of the use of clickbait is created to be able to inform about transfers or signings of players in international football.